Advanced Methodologies for Manipulating Nanoscale Features in Focused Ion Beam - Yang-Hee Kim; Jong-Hyun Seo; Ji Yeong Lee; Jae-Pyoung Ahn (한국현미경학회, 2015)
Nanomanipulators installed in focused ion beam (FIB), which is used in the lift-out of lamella when preparing transmission electron microscopy specimens, have recently been employed for electrical resistance measurements, tensile and compression tests, and in situ reactions. During the pick-up process of a single nanowire (NW), there are crucial problems such as Pt, C and Ga contaminations, damage by ion beam, and adhesion force by electrostatic attraction and residual solvent. On the other hand, many empirical techniques should be considered for successful pick-up process, because NWs have the diverse size, shape, and angle on the growth substrate. The most important one in the in-situ precedence, therefore, is to select the optimum pick-up process of a single NW. Here we provide the advanced methodologies when manipulating NWs for in-situ mechanical and electrical measurements in FIB.